Critical Public Pedagogy and Michael Moore’s Film Sicko: Creating a National Dialogue for Changing Health Care - Elizabeth J. Tisdell; Karin Sprow (Adult Education Research Conference, 2009)
This paper discusses a qualitative study exploring how health care workers view Michael Moore’s film Sicko and its role in national discussions of health care.